Responsible Programming. - Cerf, Vinton G. (Communications of the ACM, 2014)
The author focuses on the need for computer programmers to have a clear sense of responsibility for the reliable operation of the software they write and a resistance to compromise and error. He states that programmer Steve Crocker pursued a dissertation on provable correctness of programs and the complexity of tools available to programmers for validating assertions. He talks about the use of subroutine libraries in verifying program correctness and how it can assist in the validation process.